2014
DOI: 10.1071/rj13075
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of stocking methods for beef production in northern Australia: pasture and soil surface condition responses

Abstract: Historical stocking methods of continuous, season-long grazing of pastures with little account of growing conditions have caused some degradation within grazed landscapes in northern Australia. Alternative stocking methods have been implemented to address this degradation and raise the productivity and profitability of the principal livestock, cattle. Because information comparing stocking methods is limited, an evaluation was undertaken to quantify the effects of stocking methods on pastures, soils and grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In rotationally grazed systems, there are compromises and trade-offs that occur between pasture and animal production such as the lower legume levels and lower levels of per-head and per-hectare production (Saul and Chapman 2002). Hall et al (2011) compared three grazing systems, from continuous grazing through to intensive grazing, under extensive commercial conditions in Queensland and found that diet quality tended to be lower in the more intensive grazing systems. Others too have found that longer grazing rest periods can result in lower-quality herbage because of a higher proportion of stem to digestible leaf (Waller et al 2001).…”
Section: Integrative Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rotationally grazed systems, there are compromises and trade-offs that occur between pasture and animal production such as the lower legume levels and lower levels of per-head and per-hectare production (Saul and Chapman 2002). Hall et al (2011) compared three grazing systems, from continuous grazing through to intensive grazing, under extensive commercial conditions in Queensland and found that diet quality tended to be lower in the more intensive grazing systems. Others too have found that longer grazing rest periods can result in lower-quality herbage because of a higher proportion of stem to digestible leaf (Waller et al 2001).…”
Section: Integrative Discussionmentioning
confidence: 99%
“…While there are recorded cases of farm managers and proponents of intensive grazing management claiming benefits of such systems, including increased soil phosphorus, stocking rates and profits (McCosker 2000;Cawood 2004), there are also publications where some of the claims have been refuted (Waugh 1997;Dowling et al 2005;Hall et al 2011). The earliest of these papers, written by a grazier from central NSW, reported unsatisfactory cattle growth when he implemented 'time control grazing' on his property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species richness and diversity was unaffected by ReGM in sown pastures (Scott, 2001), semiarid grassland (Weigel et al, 1989;Hillenbrand et al, 2019;Oliva et al, 2021), semi-arid shrubland (Beukes and Cowling, 2000), and mesic (>650 mm a −1 MAP) grassland (Jacobo et al, 2006;Dorrough et al, 2012;Chamane et al, 2017a;Kurtz et al, 2018). Reduction in species richness under ReGM ranged from 10% (Hall et al, 2014) to over 80% (Scott-Shaw and Morris, 2015), with grasses (Allington and Vallone, 2011), forbs (Lawrence, 2019) and shrubs (McManus et al, 2018) negatively affected by intense grazing and trampling, especially during droughts (Souther et al, 2020). Regenerative grazing increased plant species (Earl et al, 2003) and life-form diversity (Barnes and Howell, 2013) over time compared to ungrazed areas (Paine and Ribic, 2002;Girard-Cartier and Kleppel, 2017) as well as to rangeland grazed continuously (Lalampaa, 2016;Odadi et al, 2017;Rantso et al, 2021;Wang et al, 2021) or rotationally at a lower intensity (Laliberté and Tylianakis, 2012).…”
Section: Plantsmentioning
confidence: 99%
“…There are various strategies and methods reduced biodiversity, diminished soil stability, impaired nutrient cycling, decreased water infiltration and greater rainfall runoff. All of these factors leave the soil susceptible to erosion, resulting in changes to soil, geomorphic and hydrological processes (Greene et al, 1994;Lal, 2010;Silburn et al, 2011;Hall et al, 2014). Degraded soil has an impaired capacity to provide ecosystem services such as water and nutrients for plant growth.…”
Section: Introductionmentioning
confidence: 99%